2018
DOI: 10.2147/cmar.s158155
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of microRNAs in cholangiocarcinoma: a systematic review and meta-analysis

et al.

Abstract: Background and aimSeveral dysregulated microRNAs (miRNAs) have been implicated in the pathogenesis of cholangiocarcinoma (CCA); however, small sample sizes and invariable research designs are limitations, hindering a thorough analysis of miRNAs as diagnostic and prognostic tools for CCA. This study aimed to systematically summarize the clinical value of miRNAs in human CCA both for all available miRNAs and single miRNA with multiple researches.MethodsPooled parameters included the area under the curve (AUC), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 57 publications
1
16
1
Order By: Relevance
“…Recently, a number of miRNAs including miR-424-5p [25] and miR-876 [26] have been reported to regulate cell proliferation, apoptosis, migration and invasion in CCA. MiR-21 is considered as a potential diagnostic and prognostic biomarker for CCA [8,9]. The plasma level of miR-21 is significantly upregulated in patients with CCA compared to healthy population [8] and CCA patients with elevated expression of miR-21 were related to poor survivals [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a number of miRNAs including miR-424-5p [25] and miR-876 [26] have been reported to regulate cell proliferation, apoptosis, migration and invasion in CCA. MiR-21 is considered as a potential diagnostic and prognostic biomarker for CCA [8,9]. The plasma level of miR-21 is significantly upregulated in patients with CCA compared to healthy population [8] and CCA patients with elevated expression of miR-21 were related to poor survivals [9].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA-21 (miR-21) is an oncogene in various types of human tumors. Recent studies indicate that miR-21 may be a potential diagnostic and prognostic biomarker for CCA [8,9]. As our previous study found that dihydromyricetin had great anti-atherosclerosis effects though regulating miR-21 [10], we were interested to investigate whether dihydromyricetin could exert anti-tumor effects in human CCA cell lines, and whether the underlying mechanism was through regulating miR-21.…”
Section: Ivyspringmentioning
confidence: 99%
See 1 more Smart Citation
“…The article, “Diagnostic and prognostic value of microRNAs in cholangiocarcinoma: a systematic review and meta-analysis”, published by Sun et al in the Cancer Management and Research journal, has caught our attention. 1 There are only few studies available on the subject of prognostic and diagnostic markers in cholangiocarcinoma, when compared with the literature available on other forms of cancer. For this reason, we believe that Sun et al’s study can be a valid reference point for future studies in this field.…”
mentioning
confidence: 99%
“…Analysis of heterogeneity between diagnostic test accuracy studies: the study by Sun et al 1 has used the Chi-squared statistics to test against the null hypothesis and the I -squared statistics to study heterogeneity, but both these statistical values do not consider the threshold effect. It might be beneficial to also include the Tau-squared statistics as a part of the statistical analysis performed in this study.…”
mentioning
confidence: 99%